Report on the Donations of Coins now added to the Society's Collection (Proceedings of the Society of Antiquaries of Scotland, 1855)
Details of various coins that were either donated to the Society or exhibited at Society events including Roman, Stuart and Indian examples. Meeting notes for February 27, 1854 are appended.